2003
DOI: 10.1097/00007435-200302000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Human Papillomavirus in a Family Planning Population in Nairobi, Kenya

Abstract: The pattern of HPV distribution in this population was different from that in other regions in the world, which has important consequences for HPV vaccine development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
64
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 26 publications
19
64
5
Order By: Relevance
“…Human papillomavirus-52, HPV-35, and HPV-58 were the most prevalent types in the present study. A high prevalence of these HPV types has been also observed in other African studies (Gravitt et al, 2000;Castellsague et al, 2001;De Vuyst et al, 2003;Mayaud et al, 2003;Xi et al, 2003;Baay et al, 2004;Thomas et al, 2004;Wall et al, 2005).…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Human papillomavirus-52, HPV-35, and HPV-58 were the most prevalent types in the present study. A high prevalence of these HPV types has been also observed in other African studies (Gravitt et al, 2000;Castellsague et al, 2001;De Vuyst et al, 2003;Mayaud et al, 2003;Xi et al, 2003;Baay et al, 2004;Thomas et al, 2004;Wall et al, 2005).…”
Section: Discussionsupporting
confidence: 73%
“…Positive HPV samples were typed by LiPA and by sequencing when LiPA was inconclusive, leaving no sample unidentified. While the epidemiology of genital HPV types has been relatively better studied in Southern and Eastern African countries such as Kenya (Temmerman et al, 1999;De Vuyst et al, 2003), Malawi (Miotti et al, 1996), Mozambique (Castellsague et al, 2001), Tanzania (Mayaud et al, 2003), Uganda (Serwadda et al, 1999), and Zimbabwe (Gravitt et al, 2002;Baay et al, 2004), data from Western Africa have been scarce. The prevalence of HPV infection and associated cervical lesions have been studied in Ivory Coast (La Ruche et al, 1998) and Mali (Bayo et al, 2002), but detailed HPV types were only reported from Senegal (Xi et al, 2003), Nigeria (Thomas et al, 2004), and The Gambia (Wall et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations